Pengembangan Media Mobile Learning Berbasis Android pada Materi Pengolahan dan Penyajian Kue Tradisional Indonesia Berbahan Dasar Tepung - Adinda Febryanti; Sachriani Sachriani; Rina Febriana (Syntax Idea)
Background, in the era of digital transformation like now in the 21st century, where information and communication technology has developed very rapidly. The use of technology is considered very important in all areas of human life to facilitate communication and information in a very wide scope and reach, quickly and easily. This research method was carried out using the research and development (r&d) method. Development research is a process used to develop and validate educational products. In this research and development, the researchers used the addie development model. The material expert trial was conducted by expert lecturers from the culinary education faculty of engineering, jakarta state university. The results of the material expert assessment instrument consisted of 3 aspects of assessment, which were divided into 13 indicators and 17 statements with a maximum score of 68 points. Material Experts, Media Experts And Linguists stated that android-based mobile learning media on the material for processing and serving traditional indonesian flour-based cakes was stated suitable for use in the learning process. The conclusion of the students stated that android-based mobile learning media on traditional cake material was declared feasible for use in the learning process